PENGARUH INDEPENDENSI, TEKANAN ANGGARAN WAKTU, RISIKO AUDIT, DAN GENDER PADA KUALITAS AUDIT - Ariningsih, Putu Setia; Mertha, I Made (E-Jurnal Akuntansi, 2017)
Quality audit is a combination of the probability an auditor to be able to find and report fraud that occurs the client’s accounting system. This study aims to obtain empirical evidence about the influence of the independence, time budget pressure, audit risk, and gender on audit quality. This research was conducted in the Public Accounting Firm (KAP) Denpasar listed in the Directory of Certified 2016. Data collection methods used in this research is survey method with questionnaire technique. The population in this study is the auditor who worked on Public Accounting Firm (KAP) Denpasar by the number of respondents was 40 auditors. The sampling method used is non-probability sampling method with saturated sampling technique. The data analysis used is multiple linear regression analysis. The analysis showed that the independent variables positive effect on audit quality, time budget pressure and the risk audit negative effect on the quality of audits.
Keywords: Independence, Time Budget Pressure, Risk Audit, Gender, Quality Audit